Implementation of Village Budget Policy: Transparency, Ac-countability, and Public Trust in Bumi Harapan Village, Tanah Laut Regency - Mohammad Yasin; Ika Devy Pramudiana; Nihayatus Sholichah; Dandy Patrija (International Journal of Social Science and Humanity, 2026)
This study aims to analyze the implementation of the Village Revenue and Expenditure Budget (APBDes) policy in Bumi Harapan Village, Tanah Laut Regency, with a focus on the pillars of transparency, accountability, and its impact on public trust. Using a descriptive qualitative method with a case study approach, this study collected data through participant observation, documentation, and in-depth interviews with key informants such as the Village Head, the Village Consultative Body (BPD), and community leaders. The results indicate that the implementation of the APBDes has met the minimum standards of good village governance through the fulfillment of formal transparency and administrative accountability. There is a strong political will from the village government to open access to budget information and high compliance with standard operating procedures (SOPs) and vertical audits from the district government. However, gaps were found in the substantive transparency dimension; the presentation of budget data through outdoor media was considered too technical and difficult for the general public to understand. Public trust in Bumi Harapan Village was proven to be multidimensional and strongly influenced by results-based legitimacy, such as tangible infrastructure improvements and fair distribution of social assistance. In addition to physical performance, the personal integrity and honesty of leadership figures are crucial factors in building village social capital. The research suggests a transformation from passive transparency to active, educational transparency through the use of simple infographics at the RT/RW level to increase the community's substantial understanding of the village budget.